Effect of Phenylglyoxal-modified α2-Antiplasmin on Urokinase-induced Fibrinolysis - Lee, Kyung N.; Lee, Steve C.; Jackson, Kenneth W.; Tae, Weon-Chan; Schwartzott, Darlene G.; McKee, Patrick A. (Thrombosis and Haemostasis, 1998)
One of the functions of activated blood clotting factor XIII (FXIIIa) is the crosslinking of α2-antiplasmin (α2AP) to fibrin. This process results in localization and concentration of α2AP throughout fibrin, thereby making fibrin more resistant to digestion by plasmin. We reasoned that competition by chemically-modified inactive α2AP (modα2AP) with native α2AP would diminish the resistance of fibrin to digestion by plasmin. Modα2AP was prepared by treating native α2AP with an Arg-specific reagent, phenylglyoxal. An average of four of the total nineteen Arg residues in α2AP reacted with phenylglyoxal and resulted in complete loss of plasmin inhibitory activity; however, modα2AP competed effectively with native α2AP for becoming crosslinked to fibrin by FXIIIa catalysis. In the presence of modα2AP, urokinase (UK)-induced plasma clot lysis time shortened significantly. Modα2AP enhanced UK-induced clot lysis in a whole blood system as shown by the similarities of rates of clot lysis for a mixture of 20 U/ml UK and 1.5 μM modα2AP versus that induced by 100 U/ml UK without modα2AP. Less fibrinogenolysis occurred in whole blood when modα2AP was present since much lower UK concentrations were needed to achieve the same level of fibrinolysis than when only native α2AP was present. Our results indicate that modα2AP enhances UK-induced fibrinolysis by competitive inhibition of factor XIIIa-mediated incorporation of native α2AP into fibrin.